Объяснение:
4Al + 3O2 = 2Al2O3
Al2O3 + 3H2SO4 = Al2(SO4)3 + 3H2O
Al2O3 + 6H(+) + 3SO4(2-)= 2Al(3+) + 3SO4(2-) + 3H2O
Al2O3 + 6H(+) = 2Al(3+) + 3H2O
Al2(SO4)3 + 6NaOH = 2Al(OH)3↓ + 3Na2SO4
2Al(3+) + 3SO4(2-)+ 6Na(+) + 6OH(-) = 2Al(OH)3↓ + 6Na(+) + 3SO4(2-)
Al(3+) + 3OH(-) = Al(OH)3↓
2Al(OH)3 -> Al2O3 + 3H2O
Al2O3 + 6HNO3 = 2Al(NO3)3 + 3H2O
Al2O3 + 6H(+) + 6NO3(-) = 2Al(3+) + 6NO3(-)+ 3H2O
Al2O3 + 6H(+) = 2Al(3+) = 3H2O
Объяснение:
4Al + 3O2 = 2Al2O3
Al2O3 + 3H2SO4 = Al2(SO4)3 + 3H2O
Al2O3 + 6H(+) + 3SO4(2-)= 2Al(3+) + 3SO4(2-) + 3H2O
Al2O3 + 6H(+) = 2Al(3+) + 3H2O
Al2(SO4)3 + 6NaOH = 2Al(OH)3↓ + 3Na2SO4
2Al(3+) + 3SO4(2-)+ 6Na(+) + 6OH(-) = 2Al(OH)3↓ + 6Na(+) + 3SO4(2-)
Al(3+) + 3OH(-) = Al(OH)3↓
2Al(OH)3 -> Al2O3 + 3H2O
Al2O3 + 6HNO3 = 2Al(NO3)3 + 3H2O
Al2O3 + 6H(+) + 6NO3(-) = 2Al(3+) + 6NO3(-)+ 3H2O
Al2O3 + 6H(+) = 2Al(3+) = 3H2O